Wiskott–Aldrich syndrome: Oral findings and microbiota in children and review of the literature. Issue 1 (24th February 2022) - Lucchese, Alessandra; Cenciarelli, Sabina; Manuelli, Maurizio; Marcolina, Marta; Barzaghi, Federica; Calbi, Valeria; Migliavacca, Maddalena; Bernardo, Maria Ester; Tucci, Francesca; Gallo, Vera; Fraschetta, Federico; Darin, Silvia; et al.
Abstract: Objective: Wiskott–Aldrich syndrome (WAS) is a rare X‐linked primary immunodeficiency, characterized by micro‐thrombocytopenia, recurrent infections, and eczema. This study aims to describe common oral manifestations and evaluate oral microbioma of WAS patients. Material and methods: In this cohort study, 11 male WAS patients and 16 male healthy controls were evaluated in our Center between 2010 and 2018. Data about clinical history, oral examination, Gingival Index (GI) and Plaque Index (PI) were collected from both groups. Periodontal microbiological flora was evaluated on samples of the gingival sulcus. Results: WAS subjects presented with premature loss of deciduous and permanent teeth, inclusions, eruption disturbance, and significantly worse GI and PI. They also showed a trend toward a higher total bacterial load. Fusobacterium nucleatum, reported to contribute to periodontitis onset, was the most prevalent bacteria, together with Porphyromonas gingivalis and Tannerella forsythia . Conclusions: Our data suggest that WAS patients are at greater risk of alterations in the oral cavity. The statistically higher incidence of periodontitis and the trend to higher prevalence of potentially pathological bacterial species in our small cohort, that should be confirmed in future in a larger population, underline the importance of dentistry monitoring as part of the multidisciplinary management of WAS patients.